The Attitude toward Teacher Digital Media in English Language Teaching - Sri Winarti; Nur Hidayanto Pancoro Setyo Putro (Journal of World Science, 2024)
The increasing integration of digital media in education has opened new pathways for enhancing student engagement, particularly in English reading classes. This study aims to explore students' attitudes toward using digital media in reading lessons, focusing on its impact on motivation and accessibility in English language learning. Utilizing a descriptive qualitative approach, this research was conducted in a State Junior High School in Sleman, with data collected from ten students through interviews, observations, and questionnaires. The data were analyzed using thematic analysis to uncover recurring patterns related to student experiences with digital media. The findings reveal that students generally respond positively to digital media, appreciating its flexibility and access to diverse reading resources. Digital media facilitates engaging, interactive learning and enables students to study independently outside the classroom, breaking the limitations of time and space. The study concludes that digital media has significant potential to enhance motivation and foster a more inclusive, accessible learning environment. However, challenges remain regarding digital literacy and consistent technology access. Future research could explore the long-term impact of digital media on reading proficiency and strategies to support broader implementation in under-resourced schools.